2012
DOI: 10.2118/161212-pa
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics-Based Study of an Oilfield Separator--Part I: A Realistic Simulation

Abstract: A realistic computational fluid dynamics (CFD) simulation of a field three-phase separator has been developed. This realistic CFD simulation provides an understanding of both the microscopic and macroscopic features of the three-phase separation phenomenon. For simulation purposes, an efficient combination of two multiphase models of the commercial CFD software, Fluent 6.3.26 (ANSYS 2006a), was implemented. The flow-distributing baffles and wire mesh demister were also modeled using the porous media model. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Hence, the sloshing in the AGRU is responsible for the decrease of removal efficiencies of CO 2 and H 2 S to 11.3% and 50%, respectively. Furthermore, if only the liquid carryover due to sloshing in multiphase separators is considered, the sweet gas production rate is 18.5 MMCFD. …”
Section: Modeling and Resultsmentioning
confidence: 99%
“…Hence, the sloshing in the AGRU is responsible for the decrease of removal efficiencies of CO 2 and H 2 S to 11.3% and 50%, respectively. Furthermore, if only the liquid carryover due to sloshing in multiphase separators is considered, the sweet gas production rate is 18.5 MMCFD. …”
Section: Modeling and Resultsmentioning
confidence: 99%
“…The developed CFD simulation of the separator could capture these field-separation problems by evaluating the mass distribution of oil and water droplets between oil and water outlets. As presented in Pourahmadi Laleh et al (2012), the overall separation efficiency of 98.0% in 1988 would decrease to 70.4% for the future-production condition. The separation efficiencies for oil and water droplets were calculated to be 100 and 96.9%, respectively, for the 1988 production condition.…”
Section: Introductionmentioning
confidence: 86%
“…A sensitivity analysis on the defined droplet-size distribution showed that separation efficiencies are not overly sensitive to the assumed maximum droplet size (Pourahmadi Laleh 2010). Therefore, the required particle-size-distribution parameters were set as estimated for the 1988 production condition (Pourahmadi Laleh et al 2012). The results are presented in Table 3.…”
Section: Cfd-based Redesign Of the Gullfaks-a Separatormentioning
confidence: 99%
See 2 more Smart Citations